Paraoxonase‐1 (PON1) Status Analysis Using Non‐Organophosphate Substrates. Issue 1 (20th January 2021) - Marsillach, Judit; Richter, Rebecca J.; Costa, Lucio G.; Furlong, Clement E.
Abstract: Human paraoxonase‐1 (PON1) is a high‐density lipoprotein‐associated enzyme with antioxidant, anti‐inflammatory, and antiapoptotic roles. The ability of PON1 to hydrolyze specific organophosphate (OP) compounds and prevent accumulation of oxidized lipids in lipoproteins has prompted a large number of studies investigating PON1's role in modulating toxicity and disease. Most of these studies, however, have only focused on PON1 single nucleotide polymorphism analyses and have ignored PON1 activity levels, arguably the most important parameter in determining protection against exposure and disease. We developed a two‐substrate activity assay termed "PON1 status" that reveals both the functional PON1192 genotype and plasma PON1 activity levels. While our previous studies with PON1 status demonstrated that both PON1192 functional genotype and enzymatic activity levels obtained exclusively by determining PON1 status are required for a proper evaluation of PON1's role in modulating OP exposures and risk of disease, the original PON1 status assay requires the use of highly toxic OP metabolites. As many laboratories are not prepared to handle such toxic compounds and the associated waste generated, determination of PON1 status has been limited to rather few studies. Here, we describe a PON1 status protocol that uses non‐OP substrates with a resolution equivalent to that of the original PON1 status approach. We have also included useful suggestions to ensure the assays can easily be carried out in any laboratory. The protocols described here will enable a proper examination of the risk of exposure or susceptibility to disease in PON1 epidemiological studies without the need to handle highly toxic substrates. © 2021 Wiley Periodicals LLC. Basic Protocol : Determining PON1 status using non‐organophosphate substrates Support Protocol 1 : Experimental pathlength determination Support Protocol 2 : PON1 DNA genotyping for the Q192R (rs662) polymorphism